Fossils and Strata : Lower Ordovician trilobites of the Kirtonryggen Formation, Spitsbergen. - Fortey, Richard A. (Fossils and Strata Monograph Series., 2013)
This monograph describes early Ordovician (Ibexian:Tremadocian-early Floian) trilobites from Northern Spitsbergen from the section through the Kirtonryggen Formation adjacent to Hinlopen Strait. The Formation is divided into three Members, each with distinct trilobites collectively representing the fullest known succession from the Bathyurid biofacies of the eastern Laurentian carbonate platform. Previous research on the Ordovician of Spitsbergen is summarised and correlations with similar faunas previously described from Canada, Greenland, western Newfoundland, Vermont-New York State, Ok.